Redefinition of the Dinoflagellate Genus Alexandrium Based on Centrodinium: Reinstatement of Gessnerium and Protogonyaulax, and Episemicolon gen. nov. (Gonyaulacales, Dinophyceae). (31st December 2019) - Gómez, Fernando; Artigas, Luis Felipe
Abstract : The genus Centrodinium contains oceanic and predominantly tropical species that have received little attention. Three species of Centrodinium were examined using thecal plate dissociation, scanning electron microscopy, and molecular sequences. The apical horn of Centrodinium intermedium and C. eminens is formed by the elongation of the fourth apical plate, and a second apical split into two plates. In C. punctatum two apical plates (2′ and 4′) almost completely encircle the apical pore plate (Po), while the contact with the plate 1′ in the ventral side is much reduced, and the plate 3′ does not reach the Po. Moreover, its left posterior lateral sulcal plate is longer than its right pair, while reversed in the typical Centrodinium spp. The sulcal posterior plate of C. punctatum is located in the left-ventral side below the plates 1′′′ and 2′′′, while the sulcal posterior plate located in the right face below the plates 4′′′ and 5′′′ in the typical Centrodinium spp. Phylogenetic analyses based on the small and large subunit of the rRNA gene showed that Centrodinium spp. and Alexandrium affine / A. gaarderae clustered as a sister clade of the Alexandrium tamarense / catenella / fraterculus groups. The clade of the subgenus Gessnerium, and the clade of the type species of Alexandrium, A. minutum, with four divergent species, clustered in more basal positions. The polyphyly of Alexandrium is solved with the split into four genera: (1) Alexandrium sensu stricto for the species of the clade of A. minutum and four divergent species; (2) the reinstatement of the genus Gessnerium for the species of the clade of A. monilatum ; (3) the reinstatement of genus Protogonyaulax for the species of the tamarense / catenella / fraterculus groups, and (4) the new genus Episemicolon gen. nov. for A. affine and A. gaarderae. New combinations in the genera Gessnerium, Protogonyaulax, and Episemicolon are proposed.